Aluminum titanium oxide alloys: Deposition of amorphous, transparent, corrosion-resistant films by pulsed DC reactive magnetron sputtering with RF substrate bias. (August 2015) - Díaz León, Juan J.; Garrett, Matthew P.; Zhang, Junce; Kobayashi, Nobuhiko P.
Abstract: Optically transparent and mechanically flexible encapsulation films are desirable for advanced optoelectronic devices. Among many variations of encapsulation, ternary metal oxide films present good optical and mechanical properties. In this study, aluminum titanium oxide (Al1− x Ti x O y ) films were deposited with a range of Ti/(Ti+Al) molar fractions ( x) using pulsed DC magnetron sputtering with RF substrate bias. Subsequently, the films were subjected to an Accelerated Weathering Environment (AWE) test at 220 °C, 1.6 atm and ~100% RH for 3 h. Optical, chemical, and morphological analyses revealed that there exists a range of Ti/(Ti+Al) molar fraction ( x =0.4–0.7) where films withstood the test, maintaining their optical, chemical, and morphological integrities. The study suggests that encapsulation films with continuously and spatially varying refractive index can be available by varying x within this range, forming encapsulation with broadband, wide angle antireflective coatings.